Prvo poročilo o gabrovi pepelovki (Erysiphe arcuata) in novi podatki o treh invazivnih pepelovkah v Sloveniji - Hauptman, Tine (Gozdarski vestnik, 2008)
The current paper is first report of powdery mildew Erysiphe arcuata on Carpinus betulus in Slovenia. It was found in arboretum Volčji Potok in 2007, afterwards also at numerous other locations throughout Slovenia and we conclude that it is widely distributed and frequent. New locations of three powdery mildews, which were introduced into Slovenia previously and are now widely distributed, are reported: Erysiphe azaleae was introduced in 2004, Erysiphe flexuosa in 2003 and Erysiphe elevata in 2003. In 2006 E. azaleae wasfound on autochtonous population of Rhododendron luteum near Boštanj. The characteristics of all four powdery mildews using Slovene material is described and their diagnostic features are presented by photographs.
Keywords: gozdovi; pepelovka; gaber; sleč; divji kostanj; ameriška katalpa